Elevated G6PD expression contributes to migration and invasion of hepatocellular carcinoma cells by inducing epithelial-mesenchymal transition. (17th February 2018) - Lu, Ming; Lu, Lu; Dong, Qiongzhu; Yu, Guangyang; Chen, Jinhong; Qin, Lunxiu; Wang, Lianxin; Zhu, Wenwei; Jia, Huliang
Abstract: Altered metabolism is one of the hallmarks of cancer cells. Pentose phosphate pathway (PPP) is a fundamental component of cellular metabolism. Glucose-6-phosphate dehydrogenase (G6PD), the rate-limiting enzyme of the PPP, is elevated in many cancers and contributes to tumor growth by producing ribose-5-phosphate and NADPH through PPP. However, the role of G6PD in hepatocellular carcinoma (HCC) metastasis and the clinical significance of G6PD in HCC progression and prognosis have not been well determined. In this study, by investigating tissue samples from HCC patients and HCC cell lines, we found that elevated G6PD expression is significantly associated with HCC metastasis and poor prognosis of HCCs, and that knockdown of G6PD inhibits in vitro proliferation, migration and invasion of HCC cell lines. Further studies reveal that G6PD contributes to HCC migration and invasion of hepatocellular carcinoma cells by inducing epithelial-mesenchymal transition through activation of signal transducer and activator of transcription 3 (STAT3) pathway. Our findings suggest that targeting G6PD could open up possibilities for metastasis intervention and improve the patients' outcomes for HCC.